Hubungan penghindaran pajak dan tanggung jawab sosial perusahaan pada perusahaan di Bursa Efek Indonesia - Susanti, Susanti; Hendi, Hendi; Krisyadi, Robby; Fathia, Yenny (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the relationship between tax avoidance and corporate social responsibility in companies on the IDX. In this study, tax avoidance, family ownership, foreign ownership, and public ownership are independent variables. CSR with the GRI 91 proxy is the dependent variable in this study. Companies listed on the Indonesia Stock Exchange (IDX) on the Indonesia Stock Exchange website (www.idx.co.id) in 2016-2020 were used in the study. The method used in sampling is purposive sampling method. The data used is the company's annual report that has been audited. Analysis of the data in this study used Eviews10 to perform an analysis that began with descriptive statistical tests, then continued with panel regression analysis and hypotheses. This study shows that tax avoidance with the ETR proxy is proven to have a positive and significant relationship to CSR. The variables of family ownership and foreign ownership are proven to have a public ownership relationship showing a negative coefficient. Firm size, firm profit, and leverage which are control variables in this study are also related to CSR.